Antibiotic prescribing practices according to the AWaRe classification among children under 5 of age attending public primary care centres in four West African countries: a cross-sectional study (AIRE project, 2021–2022) - Valéry Ridde; S Shepherd; Valériane Leroy; L Barry; M Bah; A Maïga; S Diallo; G Noel; T Sidibé; V Ridde; F Bah; Désiré Kargougou; et al. (BMJ Paediatrics Open)
Objective To describe antibiotic prescribing practices using the WHO AWaRe (Access, Watch, Reserve) classification in West African children under 5 years of age attending public primary health centres (PHCs).Design Cross-sectional study.Setting The AIRE project implemented the systematic use of pulse oximetry into integrated management of childhood illness consultations in West African countries (Burkina Faso, Guinea, Mali and Niger). We described antibiotic prescriptions for outpatient children at 16 PHCs and for severe cases referred at district hospitals.Patients Between 14 June 2021 and 19 June 2022, 15 854 outpatients were included: 968 neonates and young infants (0–28 days) and 14 886 children (2–59 months). Among them, 78 (8.1%) neonates and young infants and 385 (2.6%) children were hospitalised. We evaluated 58 hospitalised neonates and young infants and 275 hospitalised children, respectively.Main outcome measures Frequency of antibiotic prescriptions according to the AWaRe classification recommended by WHO.Results At the PHC level, proportions of neonates and young infants with ≥1 antibiotic prescription were 83%, 62%, 71% and 59% in Burkina Faso, Guinea, Mali and Niger, respectively. A total of 805 antibiotics were prescribed (85% Access and 13% Watch). The proportions of children with ≥1 antibiotic prescription reached 71%, 66%, 63% and 36% in Burkina Faso, Guinea, Mali and Niger, respectively. Out of the 9630 antibiotics prescribed, 93% were Access (mainly amoxicillin), and 7% Watch. At the hospital level, Watch antibiotics were mainly prescribed for severe cases referred. No Reserve antibiotics were prescribed.Conclusions High proportions of antibiotics were prescribed to outpatient children included, the appropriateness of which needs further study. Nevertheless, in every country, the proportion prescribed in the Access group reached the minimum threshold of 60% of all antibiotic prescriptions, as recommended by WHO.Trial registration number PACTR202206525204526.